The digital age: accuracy and excellence in oral rehabilitation - Santos Neto OM, Zavanelli RA, Zavanelli AC, Mazaro JVQ, Silva IM, Silva AO, (ARCHIVES OF HEALTH INVESTIGATION, 2019)
Digital dentistry has been gaining more and more space with investments and development of digital scanners, sensors, planning programs and CAD / CAM technologies. The digital workflow consists on the incorporation of virtual tatics to plan and execute clinical and technical procedures with emphasis on the manufacture of indirect restorations with software-based design. In addition to the quality and practicality of the rehabilitations designed using 3D CAD software, created by a 3D printer, and built in digital milling machines , there is another factor behind the growth of this market segment: the laboratory height can be reduced due to the mechanization of the processes. In this way, partial or complete treatment with virtual steps reduces clinical time, the number of steps and promotes more precise machining. The purpose of this work is to present the possibilities of digital workflow in aesthetic oral rehabilitations illustrated with clinical cases. Cases of different patients will be illustrated in order to establish the extent to which the digital workflow can be incorporated into the treatment, from a simple initial impression, to the complete rehabilitation of the patient through virtual technologies. The increasing use of the digital workflow in rehabilitation dentistry has several advantages, such as: reduction of working time and stages, better patient acceptance due to less discomfort because of procedures such as molding, greater predictability of the end of treatment and satisfactory results; however, the cost to implement this treatment is still significant. It is concluded through the cases presented that the success achieved in oral rehabilitations with digital workflow although great development, is well established. Descritores: Workflow; Rehabilitation; Dental Prosthesis.